2016
DOI: 10.1016/j.prosdent.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Customized reconstruction of an extensive mandibular defect: A clinical report

Abstract: Myoepithelial carcinomas are rare malignant tumors arising from salivary glands. They most commonly involve the parotid and minor salivary glands but may also occur in the submandibular glands. These tumors can become extensive, causing bony expansion and destruction. A 31-year-old man with a large swelling on the left side of the face is presented. Histologic examination of an incisional biopsy confirmed a diagnosis of a myoepithelial carcinoma arising from the left submandibular salivary gland. After tumor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Yet, titanium-6aluminium-4vanadium (Ti-6Al-4V) alloy is often the material of choice used to produce biomedical implant components [8][9][10][11] , prosthetic stems for total hip arthroplasties 12 , and prosthetic devices for mandible reconstructions 13,14 , due to its superior mechanical strength compared to commercially pure titanium (cpTi) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, titanium-6aluminium-4vanadium (Ti-6Al-4V) alloy is often the material of choice used to produce biomedical implant components [8][9][10][11] , prosthetic stems for total hip arthroplasties 12 , and prosthetic devices for mandible reconstructions 13,14 , due to its superior mechanical strength compared to commercially pure titanium (cpTi) 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Mandibular deformity rehabilitation is of utmost importance to restore oral function. 15 The rehabilitation of mandibular defects are challenging because in addition to the loss of anatomical structures, there is a proprioceptive loss which leads to the absence of sensation of muscles of mastication and occlusion. 16 Hence, the purpose of this report was to present a prosthetic device that would help in acquiring the normal physiological oral functions.…”
Section: Discussionmentioning
confidence: 99%
“…Upon this prototype, the definitive titanium osteosynthesis plate can be flexed, pressed, or molded preoperatively, and most notably, controlled against the stereolithographic model ( 98 ). For assisting in surgical planning and checking the fitting accuracy of the PSI preoperatively a polyamide 3D anatomic model of the remaining mandible can be fabricated by means of 3D printing (i.e., SLS) ( 99 ). Recent studies and case reports reported high accuracy levels and patient satisfaction following 3D-printed PSI, rendering 3D printing a valuable tool in up-to-date FFF reconstruction ( 100–102 ).…”
Section: Back To the Future? – Augmented Reality And Bioprinting Stra...mentioning
confidence: 99%